2013
DOI: 10.1093/nar/gkt1135
|View full text |Cite
|
Sign up to set email alerts
|

P3DB 3.0: From plant phosphorylation sites to protein networks

Abstract: In the past few years, the Plant Protein Phosphorylation Database (P3DB, http://p3db.org) has become one of the most significant in vivo data resources for studying plant phosphoproteomics. We have substantially updated P3DB with respect to format, new datasets and analytic tools. In the P3DB 3.0, there are altogether 47 923 phosphosites in 16 477 phosphoproteins curated across nine plant organisms from 32 studies, which have met our multiple quality standards for acquisition of in vivo phosphorylation site da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 43 publications
(45 reference statements)
4
42
0
Order By: Relevance
“…Thus, combining two datasets, we totally identified 6831 proteins presented in RAMs. A comparison with the Plant Protein Phosphorylation DataBase (P 3 DB) (Yao et al ., ) revealed that 1544 phosphoproteins in our RAMs dataset were absent from the current P 3 DB (Figure a). Thus, our data not only greatly enlarged the Plant Protein Phosphorylation DataBase, but also paved a way for functionally investigating proteins with phosphorylation modification during rice anther development.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, combining two datasets, we totally identified 6831 proteins presented in RAMs. A comparison with the Plant Protein Phosphorylation DataBase (P 3 DB) (Yao et al ., ) revealed that 1544 phosphoproteins in our RAMs dataset were absent from the current P 3 DB (Figure a). Thus, our data not only greatly enlarged the Plant Protein Phosphorylation DataBase, but also paved a way for functionally investigating proteins with phosphorylation modification during rice anther development.…”
Section: Resultsmentioning
confidence: 85%
“…Searches of the Arabidopsis Protein Phosphorylation Site Database (PhosPhAt 4.0) and Plant Protein Phosphorylation Database (P3DB) identified five (S195, S438, S436, S440, and S974) experimentally determined phosphorylation sites within KEG (Gao et al, 2009; Durek et al, 2010; Yao et al, 2012, 2014; Supplementary Figure S1A ). To determine if these amino acids may represent relevant and conserved phosphorylation sites we compared KEG amino acid sequence to those from nine other plant species ( Supplementary File S1 and Figures S1B , 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several structure-related PPI databases have been established (Higurashi et al 2009;Mosca et al 2013;Yao et al 2014). However, there is still room for improvement.…”
Section: Introductionmentioning
confidence: 99%